Monitoring Silent Spillovers Before Emergence: A Pilot Study at the Tick/Human Interface in Thailand - Temmam, Sarah; Chrétien, Delphine; Bigot, Thomas; Dufour, Evelyne; Petres, Stéphane; Desquesnes, Marc; Devillers, Elodie; Dumarest, Marine; Yousfi, Léna; Jittapalapong, Sathaporn; Karnchanabanthoeng, Anamika; Chaisiri, Kittipong; et al. (Frontiers in Microbiology, 2019)
Emerging zoonoses caused by previously unknown agents are one of the most important challenges for human health because of their inherent inability to be predictable, conversely to emergences caused by previously known agents that could be targeted by routine surveillance programs. Emerging zoonotic infections either originate from increasing contacts between wildlife and human populations, or from the geographical expansion of hematophagous arthropods that act as vectors, this latter being more capable to impact large-scale human populations. While characterizing the viral communities from candidate vectors in high-risk geographical areas is a necessary initial step, the need to identify which viruses are able to spill over and those restricted to their hosts, have recently emerged. We hypothesized that currently unknown tick-borne arboviruses could silently circulate in specific biotopes where mammals are highly exposed to tick bites, and implemented a strategy that combined high-throughput sequencing with broad range serological techniques to both identify novel arboviruses and tick-specific viruses in a ticks/mammals interface in Thailand. The virome of Thai ticks belonging to the Rhipicephalus, Amblyomma, Dermacentor, Hyalomma, and Haemaphysalis genera identified numerous viruses, among which several viruses could be candidates for future emergence as regards to their phylogenetic relatedness with known tick-borne arboviruses. Luciferase immunoprecipitation system targeting external viral proteins of viruses identified among the Orthomyxoviridae, Phenuiviridae, Flaviviridae, Rhabdoviridae and Chuviridae families was used to screen human and cattle Thai populations highly exposed to tick bites. Although no positive serum was detected for any of the six viruses selected, suggesting that these viruses are not infecting these vertebrates, or at very low prevalence (upper estimate 0,017% and 0,047% in humans and cattle, respectively), the virome of Thai ticks presents an extremely rich viral diversity, among which novel tick-borne arboviruses are probably hidden and could pose a public health concern if they emerge. The strategy developed in this pilot study, starting from the inventory of viral communities of hematophagous arthropods to end by the identification of viruses able (or likely unable) to infect vertebrates, is the first step in the prediction of putative new emergences and could easily be transposed to other reservoirs/vectors/susceptible hosts interfaces.